Juridical Analysis Of The Use Of Dna Forensic Evidence In The Indonesian Criminal Justice System - Wijoyo, Suryo; Suparno, Suparno (Jurnal Locus Penelitian dan Pengabdian, 2024)
The use of forensic DNA evidence in the criminal justice system in Indonesia faces various challenges, especially related to regulations that are not fully aligned with international standards. Law No. 8 of 1981 concerning the Criminal Procedure Code (KUHAP), especially Articles 184 and 186, does not provide specific guidelines regarding the procedures for collecting, testing, and using forensic DNA evidence in the criminal evidence process. This study aims to analyze the regulations and procedures governing forensic DNA evidence in Indonesia and propose legal solutions to strengthen the regulations to comply with international standards. This study uses a normative legal research method, focusing on the analysis of relevant laws, legal doctrines, and court decisions. Discussions center on the harmonization of national regulations with international standards, strengthening the capacity of forensic institutions, and reforming legal procedures related to DNA evidence. The research findings indicate that Indonesia needs more comprehensive regulatory reforms related to the use of forensic DNA evidence, especially regarding the accreditation of forensic laboratories according to international standards such as ISO 17025 and the development of transparent and legally accountable evidence collection procedures. In conclusion, although DNA evidence has great potential to strengthen convictions in the criminal justice system, regulatory reform and strengthening of forensic institutions are needed for the Indonesian justice system to adopt higher international standards. Thus, the use of forensic DNA evidence can contribute significantly to justice in criminal law enforcement in Indonesia.